2017
DOI: 10.1002/hup.2624
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of the alcohol hangover state: Ethyl glucuronide (EtG) and ethyl sulfate (EtS)

Abstract: IntroductionThe aim of this study was to investigate the usefulness of ethyl glucuronide (EtG) and ethyl sulfate (EtS) as biomarkers of the hangover state.MethodsThirty‐sixhealthy social drinkers participated in this study, being of naturalistic design. Eighteen participants experience regular hangovers (the hangover group), whereas the other 18 claim to not experience a hangover (the hangover‐immune group). On a control day (alcohol‐free) day and a post‐alcohol day, urine EtG and EtS concentrations were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Further, there were no differences in reported behaviors during the alcohol consumption sessions (e.g., dancing, sitting in a bar). Morning assessments of urine methanol [ 33 ] and urine ethyl glucuronide (EtG) and ethyl sulfate (EtS) [ 34 ] did not reveal any significant differences between the hangover-sensitive and -resistant groups. However, urine ethanol concentration was significantly lower in the hangover-resistant group when compared to the hangover-sensitive group [ 35 ], suggesting accelerated alcohol metabolism among hangover-resistant drinkers.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there were no differences in reported behaviors during the alcohol consumption sessions (e.g., dancing, sitting in a bar). Morning assessments of urine methanol [ 33 ] and urine ethyl glucuronide (EtG) and ethyl sulfate (EtS) [ 34 ] did not reveal any significant differences between the hangover-sensitive and -resistant groups. However, urine ethanol concentration was significantly lower in the hangover-resistant group when compared to the hangover-sensitive group [ 35 ], suggesting accelerated alcohol metabolism among hangover-resistant drinkers.…”
Section: Discussionmentioning
confidence: 99%
“…Even after the acute intoxication has worn off and blood alcohol levels (BAC) have returned to 0.00% , cognitive, attentional, and psychomotor functions likely remain impaired to a certain degree [6][7][8][9][10][11]. While there is currently no neurobiochemical marker that could help to reliably detect the presence of alcohol hangover [12], being hungover may not only be disastrous for driving a vehicle, but also for various daily activities including safety-sensitive tasks at work and at home. Surprisingly, the mechanisms underlying such hangover-associated behavioral deficits are still not very well understood, as compared to the effects of acute intoxication.…”
Section: Introductionmentioning
confidence: 99%
“…Data show that this claim heavily depends on how much alcohol drinkers consume, but even at higher eBAC levels a small proportion of drinkers claim not to have hangovers [27,28]. At the same time, other hangover research showed no significant differences between the two groups of drinkers on several biomarkers such as urine ethyl glucuronide (EtG) and ethyl sulfate (EtS) [57] or methanol [58], saliva cytokine levels [59], sensitivity to acute alcohol effects [60], demographics [31], or psychological characteristics such as mental resilience [61]. Additionally, the current study could not differentiate hangover-sensitive and hangover-resistant drinkers based on their dietary nutrient intake.…”
Section: Discussionmentioning
confidence: 99%